A Legal Analysis of the Role of PPNS in Health-Related Criminal Cases Concerning Systems that Ensure Patient Safety - Agung Bintartho; Subekti Subekti; Fathul Hamdani; Renda Aranggraeni (Eduvest - Journal of Universal Studies, 2026)
Patient safety has become a fundamental principle in modern healthcare systems and constitutes an essential aspect of the protection of the right to health. Nevertheless, the increasing number of health-related criminal cases, medical negligence disputes, and violations of healthcare service standards indicates that the implementation of patient safety systems in Indonesia continues to face significant juridical and institutional challenges. Under these circumstances, Civil Servant Investigators (Pejabat Pegawai Negeri Sipil or PPNS) hold a strategic position in enforcing health criminal law and ensuring compliance with healthcare regulations. This research aims to analyze the juridical role of PPNS in the enforcement of health criminal law related to patient safety systems in Indonesia. The research employs a normative juridical method using statutory and conceptual approaches. The legal materials consist of primary legal sources, including the Criminal Procedure Code and Law Number 17 of 2023 concerning Health, as well as secondary legal materials such as legal doctrines, scientific journals, and academic literature related to health law and patient safety. The findings demonstrate that PPNS possesses strategic authority not only in conducting criminal investigations, but also in carrying out preventive supervision to minimize risks to patient safety. However, the implementation of PPNS authority remains constrained by overlapping institutional authority, limited human resources, weak inter-agency coordination, and the absence of comprehensive technical regulations concerning patient safety incident investigations. Therefore, strengthening regulatory harmonization, improving PPNS competence, and developing a patient safety-oriented law enforcement model are necessary to ensure effective legal protection and improve healthcare quality in Indonesia.